2004
DOI: 10.1007/s00424-003-1106-z
|View full text |Cite
|
Sign up to set email alerts
|

A current review of fatty acid transport proteins (SLC27)

Abstract: Long-chain fatty acids (LCFAs) are not only important metabolites but contribute to many cellular functions including activation of protein kinase C (PKC) isoforms and nuclear transcription factors such as peroxisome proliferator-activated receptors (PPAPs). To assert their diverse effects LCFAs have first to traverse the plasma membrane, a process that can occur either through diffusion or be mediated by proteins. Considerable evidence has accumulated to show that in addition to a diffusional component, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 47 publications
4
203
1
1
Order By: Relevance
“…2g). Next, we examined mRNA expressions of FA transport proteins (FATP) 1, 3 and 4, which have a role in the uptake of long-chain FAs 20,21 . As shown in Fig.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…2g). Next, we examined mRNA expressions of FA transport proteins (FATP) 1, 3 and 4, which have a role in the uptake of long-chain FAs 20,21 . As shown in Fig.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…3 The identification of mammalian fatty acid transport proteins and associated acyl-CoA synthetases has strengthened the argument for protein-mediated transcellular fatty acid transport. 4 The data in ECs, however, remain scant. siRNA experiments in cell culture have indicated that fatty acid transport proteins 3 and 4 are required for VEGFB and 3-HIB (hydroxyisobutyrate)-induced endothelial fatty acid uptake, 1,2 but how these proteins function remains largely unknown.…”
Section: Article See P 1289mentioning
confidence: 99%
“…2 compose a family of transmembrane proteins that facilitate cellular long chain fatty acid uptake (1)(2)(3). The most widely expressed member of this family is FATP4 (4,5), which is encoded by Slc27a4 (solute carrier family 27 member 4 gene).…”
Section: Fatty Acid Transport Proteins (Fatps)mentioning
confidence: 99%